OFDI Agglomeration and Chinese Firm Location Decisions under the “Belt and Road” Initiative - Liu, Haiyue; Jiang, Jie; Zhang, Lei; Chen, Xiaolan (Sustainability, 2018)
This paper established a combined dataset from 2004 to 2015 for 129 host countries and matched them with 1193 Outward Foreign Direct Investment (OFDI) events by Chinese listed firms. Four variables were designed to proxy the agglomeration effects of Chinese OFDI at both an industry and country level. Probit and FGLS estimation methods were used to analyze whether the Chinese listed firm location choices were affected by the agglomeration level. It was found that the agglomeration effect of Chinese OFDI on host country selection was obvious, as Chinese firms were often found to follow other Chinese firms and invest in host countries where Chinese investment was concentrated; however, it was also found that Chinese firms did not choose countries where there was a high concentration of non-Chinese FDI. The agglomeration effect on Chinese OFDI industry selection was also significant. Firms were found to invest in industries that already had large Chines OFDI agglomeration or high host-country industrial agglomeration. Further investigations found that the “Belt and Road” Initiative (BRI) was effective in guiding location decisions. Firms were found to invest more along the “Belt and Road” route after the BRI was launched; however, large State-owned listed firms with higher leverage but lower productivity and profitability were found to more often invest along the BRI routes.